Calidad de atención y grado de satisfacción del usuario externo del servicio de emergencia de una institución de salud III, Iquitos 2022 - Cahuachi Alves, Roy Roger (2024)
The present study, titled "Quality of Care and Degree of Satisfaction of the External User of the Emergency Service of a Health Institution III, Iquitos 2022", aimed to determine the quality of care and the degree of satisfaction of the external user who uses the emergency service of a level III health institution. The method used was a descriptive, cross-sectional correlational method, with a population of 3776 and a sample of 124 external users of the emergency service. For data collection, the SERVQUAL survey was used to evaluate the quality of care and the Modified SERVPEF scale, currently used by the MINSA, to evaluate external user satisfaction. The results were: that of 100% (124) of the users surveyed, 59.7% (74) received poor quality of care; while 40.3% (50) received good quality of care. Regarding user satisfaction, 56.5% (70) are dissatisfied, while 43.5% (54) report being satisfied. When performing the statistical analysis to determine the relationship between the variables, X2 = 80.007 was obtained, df = 1, p = 0.000; Concluding that if there is a relationship between the variables; Therefore, the hypothesis is accepted: "There is a relationship between the Quality of Care and the degree of satisfaction of the external user who goes to the emergency service of a Health Institution III, Iquitos 2022."